Pengaruh edukasi menggunakan Lampu (lembar edukasi masyarakat di posyandu) terhadap pengetahuan dan sikap kader terkait pemberian makan bayi dan anak - Christy, Sarah; Norfiana, Ovi; Ayuningtyas, Putri (UHAMKA PRESS, 2025)
Appropriate feeding behavior for infants and young children (IYCF) aged 0-24 months is one of the keys for preventing malnutrition. A proper implementation of IYCF begins with sufficient knowledge and a positive attitude. Community-based efforts are needed to increase the knowledge and positive attitudes, one of which is through the Integrated Service Post (Posyandu) institution. Cadres play an important role in providing health information to the community. This research aims to assess the effect of education using flipchart media on the knowledge and attitudes of cadres in Petamburan Village, Tanah Abang District, Central Jakarta. This study implemented a quasi-experimental design with a one group pretest-posttest design without control which was carried out in October 2024. The research sample was taken using a random sampling technique with a total of 40 subjects. Knowledge and attitude data were obtained through a structured online questionnaire which had been statistically tested for internal consistency. The results showed that there was a change in knowledge scores before (54.54 (18.18-100)) and after being given education (81.82 (27-100)) with a significant increase in scores (p<0.001). Statistical tests on attitudes did not show significant results (p = 0.494) although there was an increase in cadres' attitude scores after (80.85 ± 12.36) and before (79.45 ± 11.75) the education. Thus, giving education using flip-chart media can increase the knowledge cadres regarding complementary feeding.